PENGARUH KENAIKAN SUKU BUNGA BI DAN INFLASI TERHADAP KINERJA KEUANGAN BANK SYARIAH - Dwi Utami Yesika; Sukamto (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2020)
Absract: The reality of the increase in world oil prices has prompted the Indonesian government to adopt a policy of increasing the price of fuel oil (BBM) which has caused the Indonesian economy to experience a drastic decline. The increase in fuel prices will be followed by an increase in the price of goods and services. This has caused the inflation rate in Indonesia to decline and further complicate the economic conditions of the people. Since the inflation rate has increased due to the government's policy of raising fuel prices, one of the steps taken by Bank Indonesia to control the inflation rate is to raise interest rates. However, in Islamic law, to avoid operating a bank with an interest system, Islam introduces the principles of muamalat as an alternative to banking in the form of Islamic banking business activities. The approach used by the author in this study is a quantitative approach with descriptive and regional methods by comparing one variable with another. So the appropriate collection technique is library research is to collect articles, journals, books and so on. The results showed that there was an influence between the increase in BI interest rates and inflation on the financial performance of syari'ah banks and there were several factors that influenced the increase in interest rates, among others: the need for funds, competition, government policies, etc. Several factors that influence inflation include: money supply, gross domestic product, exchange rates and interest rates.